2018
DOI: 10.3390/ijms19061554
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Processes Driving IgE Sensitisation and Disease Development in Males and Females

Abstract: IgE sensitisation has increased significantly over the last decades and is a crucial factor in the development of allergic diseases. IgE antibodies are produced by B cells through the process of antigen presentation by dendritic cells, subsequent differentiation of CD4+ Th2 cells, and class switching in B cells. However, many of the factors regulating these processes remain unclear. These processes affect males and females differently, resulting in a significantly higher prevalence of IgE sensitisation in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 215 publications
(234 reference statements)
1
40
0
1
Order By: Relevance
“…We found that people with high level of IgE have a higher risk of KS; however, this relationship is profoundly confounded by sex and HIV. Studies on humans and animal models show that males have higher IgE responses than females after sensitization . Persons with HIV, particularly men, have high level of IgE independently of antiparasitic or allergic responses, and IgE levels correlate with HIV disease progression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that people with high level of IgE have a higher risk of KS; however, this relationship is profoundly confounded by sex and HIV. Studies on humans and animal models show that males have higher IgE responses than females after sensitization . Persons with HIV, particularly men, have high level of IgE independently of antiparasitic or allergic responses, and IgE levels correlate with HIV disease progression .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on humans and animal models show that males have higher IgE responses than females after sensitization. 46 Persons with HIV, particularly men, have high level of IgE independently of antiparasitic or allergic responses, and IgE levels correlate with HIV disease progression. 47 Still, in our study, restricting to HIV-uninfected men, levels of IgE were related to KS and higher IgE were associated with higher anti-KSHV antibodies.…”
Section: Ige: a Marker Of Parasitic Exposure Or Immune Dysregulation?mentioning
confidence: 99%
“…Studies have shown that sex hormones can affect airway tone and inflammation, and exert effects in different lung cell types, including airway smooth muscle, 121 and immune cells, 48,122,123 although these effects are still under investigation. In the next paragraphs, we discuss the available literature on the effects of sex hormones on the key cell players of lung immunity.…”
Section: Influence Of Sex Hormones In Lung Immune Cellsmentioning
confidence: 99%
“…Until puberty, they also show a higher prevalence of clinical manifestations, but after puberty females overtake them in the incidence of allergic symptoms. The IgE levels are influenced by the mestrual cycle, suggesting a role of sexual hormones [4]. Female and male differences in allergic responses may be affected by both gender and sex.…”
Section: Introductionmentioning
confidence: 99%